Comparison of gene expression in the red imported fire ant (Solenopsis invicta) under different temperature conditions - Mohammad Vatanparast (Nature Portfolio, 2021)
Abstract The red imported fire ant (RIFA), Solenopsis invicta Buren is native to South America and is known as a global problematic invasive species. This study focused on the molecular response of RIFA by comparing gene expression profiles after exposing ants to low (10 °C) and high (40 °C) temperature stress and comparing them to untreated controls (30 °C). A total of 99,085 unigenes (the clustered non-redundant transcripts that are filtered from the longest assembled contigs) were obtained, of which 19,154 were annotated with gene descriptions, gene ontology terms, and metabolic pathways. 86 gene ontology (GO) functional sub-groups and 23 EggNOG terms resulted. Differentially expressed genes (DEGs) with log2FC ≥ 10 were screened and were compared at different temperatures. We found 203, 48, and 66 specific DEGs co-regulated at 10, 20, and 40 °C. Comparing transcriptome profiles for differential gene expression resulted in various DE genes, including cytochrome P450, NADH dehydrogenase subunit 1, cuticle protein and heat shock protein (HSP), which have previously been reported to be involved in cold and high temperature resistance. GO analysis revealed that antioxidant activity is up-regulated under high temperature stress. We verified the RNA-seq data by qPCR on 20 up- and down-regulated DEGs. These findings provide a basis for future understanding of the adaptation mechanisms of RIFA and the molecular mechanisms underlying the response to low and high temperatures.